Transglutaminase 3 reduces the severity of psoriasis in imiquimod-treated mouse skin - Piro, MC; Ventura, A; Smirnov, A; Saggini, A; Lena, AM; Mauriello, A; Bianchi, L; Melino, G; Candi, E (MDPI, 2020)
Four transglutaminase (TG) isoforms have been detected in epidermal keratinocytes: TG1, TG2, TG3, and TG5. Except for TG1 and TG3, their contribution to keratinocyte development and structure remains undefined. In this paper, we focused on the roles of TG2 and TG3 in imiquimod-induced psoriasis in mouse skin. We evaluated the severity of psoriasis markers in the skin of imiquimod-treated TG3 null and TG2 null mice. Our results showed that compromised TG3KO mouse skin was more responsive than WT or TG2KO mouse skin to the action of the pro-inflammatory drug imiquimod.